Study on the growth and development of brinjal shoot and fruit borer with different diets - Rahman, Mohammad Mahmudur; Tengku Muda Mohamed, Mahmud; Hasan, Md. Fakhrul; Habib, Sheikh Hasna; Kausar, Hossain (Academic Journals, 2011)
A laboratory experiment was conducted with two natural and one artificial diet on the growth and development of brinjal shoot and fruit borer (BSFB). The population of BSFB used in the study was in the 2nd instar larvae. Among the different diet, brinjal was the best for growth, development and longevity of larvae and pupae and prolongation of larval and pupal period. The mean length of full grown larvae fed with natural the food brinjal were 9.37, 9.80 and 12.44 mm from generations 1, 2 and 3, respectively. The larval and pupal duration on brinjal food media were 13.10 and 8.17, 12.80 and 8.23 and 13.10 and 8.03 days in generations 1, 2 and 3, respectively. The percentages of adult emergence from pupae raised in brinjal were 65.38, 47.95 and 33.78 in generations 1, 2 and 3, respectively.